Operative Time and Flap Failure in Unilateral and Bilateral Free Flap Breast Reconstruction - Kwok, Alvin C.; Edwards, Kyle; Donato, Daniel P.; Tatro, Eric; Xu, Yizhe; Presson, Angela P.; Agarwal, Jayant P. (Journal of Reconstructive Microsurgery, 2018)
Background There is an increasing trend toward bilateral breast reconstruction. Using the National Surgical Quality Improvement Program (NSQIP) database, we sought to understand the association between unilateral and bilateral free flap breast reconstruction and operative time and flap failure.Methods We selected a cohort of patients undergoing free flap breast reconstruction using the 2005 to 2010 NSQIP database. Cases were divided into unilateral and bilateral reconstruction. Subgroup analyses were performed dividing cases into delayed and immediate reconstruction. The effect of patient characteristics including age, body mass index (BMI), history of diabetes, and the American Society of Anesthesiologists' classification on operative time and flap failure was examined using univariable and multivariable regression models. Rates and odds ratios (OR) were reported using the multivariable gamma and logistic regression models, respectively.Results There were 691 free flap breast reconstructions performed in the cohort and 29.1% were bilateral cases. There was a 78-minute increase in the median operative time when comparing unilateral and bilateral reconstruction (p = 0.005). Patients undergoing bilateral reconstructions were generally younger and had fewer comorbidities compared with unilateral reconstructions. There was no significant association between bilateral reconstruction and flap failure. Immediate bilateral reconstructions had a significant increase in median operative time compared with immediate unilateral reconstructions (563 versus 480 minutes, p = 0.002) but no significant increase in operative time was noted when comparing delayed unilateral and delayed bilateral reconstructions. Prolonged operative time was associated with flap failure after adjusting for age and BMI (OR 1.17, p < 0.001).Conclusions Bilateral free flap breast reconstruction can be performed safely despite an increase in operative time when compared with unilateral reconstruction.
Keywords: breast reconstruction; free flap failure; operative time